2015
DOI: 10.4103/0022-3859.150444
|View full text |Cite
|
Sign up to set email alerts
|

An audit of histopathology reports of carcinoma endometrium

Abstract: Background:The aim was to see, compliance to minimum data information in carcinoma endometrium reports, in a team of 13 pathologists, and also to analyze these parameters e.g. tumor size, type, grade, depth of myometrial invasion, lymph node yield, pTNM stage etc.Materials and Methods:Reports of 114 cases of carcinoma endometrium, that were operated in-house during the years 2008 to 2010 were analyzed from the files of the Pathology department of our hospital.Results:The median age was 58.04 years and median t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
1
1
0
Order By: Relevance
“…Out of total 542 cases, 12 (2.21%) cases of endometrial malignancies were observed, similar observation was found in other studies by Pessoa et al [12] & Zill-E-Huma et al [10] In present study, most common type of endometrial malignancy was endometrioid adenocarcinoma comprised of 7 out of 12 (58.34%) cases, which was comparable with studies done by Himel B et al [19] and Deodhar KK et al [18].…”
Section: Original Research Articlesupporting
confidence: 92%
“…Out of total 542 cases, 12 (2.21%) cases of endometrial malignancies were observed, similar observation was found in other studies by Pessoa et al [12] & Zill-E-Huma et al [10] In present study, most common type of endometrial malignancy was endometrioid adenocarcinoma comprised of 7 out of 12 (58.34%) cases, which was comparable with studies done by Himel B et al [19] and Deodhar KK et al [18].…”
Section: Original Research Articlesupporting
confidence: 92%
“…Further, a report published in J Clin Pathology[ 3 ] has also reflected on audit reports[ 4 5 ] which have been based more on descriptive reporting, as has been used by the authors of this study. [ 1 ] This report concluded that a pure descriptive procedure was inefficient and of limited educational value. This is also evident from the conclusion drawn by the authors.…”
mentioning
confidence: 99%